Parent-Reported Symptoms of Sleep-Disordered Breathing Are Associated With Increased Behavioral Problems at 2 Years of Age: The Canadian Healthy Infant Longitudinal Development Birth Cohort Study. Issue 1 (1st November 2017) - Tamana, Sukhpreet K; Smithson, Lisa; Lau, Amanda; Mariasine, Jennifer; Young, Rochelle; Chikuma, Joyce; Lefebvre, Diana L; Subbarao, Padmaja; Becker, Allan B; Turvey, Stuart E; Sears, Malcolm R; ,; et al.
Abstract: Study Objectives: To examine the association between the age of onset and duration of parent-reported symptoms of sleep-disordered breathing (SDB) and behavioral problems at age 2. Methods: Parent-reported SDB symptoms were assessed quarterly between 3 months and 2 years among 583 Canadian Healthy Infant Longitudinal Development Edmonton-site participants. Parent-reported SDB symptoms were clustered into phenotypes using group-based trajectory analysis based on age of onset and duration of symptoms. Home-based polysomnography (PSG) was completed at 1 year. The Child Behavior Checklist preschool-version (Mean T -score 50, standard deviation 10 points) assessed total, externalizing (attention), and internalizing (anxiety, depression) behaviors at 2 years. Results: Four phenotypes were identified: no SDB (64.7%), early-onset SDB (15.7%, peak symptoms at 9 months), late-onset (14.2%, peak symptoms at 18 months), and persistent SDB symptoms (5.3%, peak symptoms from 3 through 24 months). Persistent SDB (9.5 points, 95% CI 1.7, 17.2; p = .02) predicted the greatest magnitude of effect of total behavior problems, compared with children without SDB. Children with early-onset SDB (3.5 points, 95% CI 1.6, 5.4; p ≤ .001) and late-onset SDB (6.1 points 95% CI 4.0, 8.3; p ≤ .001) had increased total behavioral problems than children without SDB to 2 years. Additional analyses showed that the SDB phenotypes' trajectories were important for internalizing but not for externalizing behavior problems. There were no significant associations between home-PSG and parent-reported behavior problems. Conclusions: Findings suggest that the age of onset and duration of parent-reported SDB symptoms prior to age 2 have adverse consequences for overall behavior problems.